Review of the leafhopper genus Oncopsis Burmeister (Hemiptera: Cicadellidae: Macropsinae) in China with descriptions of two new species - Yang, Liyuan; Zhang, Yalin (Zootaxa, 2015)
Two new macropsine species, Oncopsis latusoid sp. nov. and O. taibaiensis sp. nov. are described and illustrated from China. A checklist and illustrated key to Chinese species of this genus are given.